Pemberdayaan UMKM melalui Pelatihan Desain Produk dan Digital marketing di Kelurahan Mojo, Kecamatan Gubeng, Kota Surabaya - Jamiatun Juliana; Azmil Umur; Renata Nanda Swastika; Santi Dewi Lestari; Intania Widyantari Kirana (Komunitas Dosen Indonesia, 2025)
Mojo Subdistrict in Surabaya is one of the areas with great potential for the development of Micro, Small, and Medium Enterprises (MSMEs), particularly in the culinary, handicraft, and household product sectors. However, MSME actors still face several challenges such as limited knowledge of digital marketing, unrepresentative business locations, unattractive packaging designs, and suboptimal branding and social media management. This community service activity aimed to enhance the capacity of MSME actors through training in product design and digital marketing, using methods such as material presentation, visual design creation, social media content development, and registration on e-commerce platforms. The results showed improvements in decision-making abilities, business management, and awareness of the importance of brand identity and product legality. Moreover, positive developments were observed in active participation and collaboration among MSMEs, although collective cohesion still requires improvement. Overall, this program had a tangible impact on strengthening the independence and competitiveness of local MSMEs in a more professional and sustainable manner.